Manajemen Kepemimpinan Kepala Sekolah SD GMIM 60 Pinilih dan SD GMIM 61 Klabat - Jastila Kamagi; Jeane M. Tulung; Anita I. Tuela (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study, is to obtain results of analysis and description of data about the leadership management of school principals at SD GMIM 60 Pinilih and SD GMIM 61 Klabat, the factors that prevent principals from perfoming their management responsibilities effectively there, and the effects of principal leadership management on caliber of primary school instruction there.To achieve the research objectives, the researchers used a qualitative approach with descriptive analytical methods by following Milles and Huberman's design for data collection, which included observation, interviews, and document studies, the researchers used a qualitative approach with descriptive analytical methods to meet their goals.The data were then analyzed using multiple-stage analytical procedures, including reduction, data presentation, and conclusion drawing. Based on the study's findings, the researchers came to the following conclusions:(1)Different leadership management strategies were implemented in SD GMIM 60 Pinilih and SD GMIM 61 Klabat even though they shared an educational foundation;(2)The inhibiting factor that was encountered was the principal's own lack of discipline, firmness, and efforts to resolve financial and educational issues; and (3) The impact of principal leadership management has an impact on the quality of education in SD GMIM 60 Pinilih and SD GMIM 61 Klabat.